The relationship between corporate social disclosure and Islamic unit trust shareholdings - Yahya, Mohd Azlan; Abdul Rahman, Azhar; Tayib, Mohamad (2004)
In recent years, the impressive growth of Islamic funds provides an avenue for researcher to study institutional investment decision from the Islamic perspective.The purpose of this study is to examine the relationship between corporate social performance(CSP) and Islamic unit trust shareholdings in Shari'ah based companies in Malaysia.We measure CSP using the corporate social disclosure levels that are constructed based on three attributes of corporate social activities, namely social commitment, employee welfare, and environmental concern. The sample comprises of 194 companies listed on the main board of the Kuala Lumpur Stock Exchange Islamic Index.In this study we hypothesize that Islamic unit trusts invest heavily in companies with high levels of corporate social disclosure.Descriptive analysis shows that only 102 companies disclose their social activities in which 68 companies disclose only one attribute, 12 companies disclose two attributes, and 22 companies disclose all attributes of corporate social disclosure.The t-test shows that there is a significant difference in corporate social disclosure between companies invested and those that are not invested by Islamic unit trusts.The result of the regression analysis indicates that there is a significant, positive relationship between the levels of corporate social disclosure and the number of Islamic unit trusts holding the share of a company, thus supporting our hypothesis.In addition, it also indicates that Islamic unit trusts try to avoid from investing in risky companies.The result shows that there is a negative relationship between leverage but a significant, positive relationship between size and the number of Islamic unit trusts holding the share of a company.This implies that as religious based investment institutions, Islamic unit trusts attempt to fulfill its investment objectives not only to gain financial benefits but also to achieve 'falah'(success) according to Islamic investment objectives which emphasize on social well being and risk avoidance.The implication of this research is twofold. Firstly, it may provide an empirical justification to the Islamic economic theory arguments that 'Islamic economic man' is different from the conventional 'economic man' in the context of investment decision. Secondly, it also provides a signal to managers of companies to give serious consideration in inculcating and enhancing their social commitment if they want their companies to be attractive to Islamic unit trust.